Tropes and territories : short fiction, postcolonial readings, Canadian writing in context - Dvorak, Marta; New, W. H. (William Herbert), 1938- (McGill-Queen's University Press, 2007)
"Postcolonial and Commonwealth literary scholarship has tended to emphasize the novel. Tropes and Territories is the first book to focus on modern short fiction, including Metis narratives, Maori myth, and stories by Mansfield, Frame, Munro, Rushdie, MacLeod, Gallant, Narayan, Jarman, and King. While Canadian writers and writings are central, contributors also consider South Pacific, South Asian, and Caribbean stories." "Tropes and Territories demonstrates how current debates in postcolonial criticism bear on the reading, writing, and status of short fiction. These debates, which hinge on competing definitions of "trope" (motif vs rhetorical turn) and "territory" (political or aesthetic), lead to studies of space, place, influence, and writing and reading practices across cultural divides. The essays also explore the character of diasporic writing, the cultural significance of oral taletelling, and interconnections between socio/political issues and strategies of style."--Jacket